Anthropometric Indicators to Determine the Obesity and its Relations with the Cardiometabolic Risk - Raúl Cedeño Morales; Maricel Castellanos González; Mikhail Benet Rodríguez; Luis Mass Sosa; Carlos Mora Hernández; Jorge Carlos Parada Arias (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
Background: it has become a controversy if obesity per se is an independent cardiometabolic risk factor it self or it influences like a contributing element of other factors, specially hypertension, insulin resistance and dislipidemias. Objective: determining which of the anthropometric parameters used to quantify obesity is more associated to the cardiometabolic risk factors. Methods: a correlational and descriptive study in 105 workers of the Medical Sciences University of Cienfuegos from June 2011 to July 2013. There were operationalized like clinical variables: measurement of the abdominal waist, index of corporal mass, cutaneous crease and blood pressure; and like variables of laboratory: total cholesterol, HDL cholesterol, glucemia and tri-glycerides. It was calculated the correlation coefficient of Pearson with 95 % confidence interval. Results: it was evidenced a light increment of total cholesterol in individuals of the masculine sex at expense of HDL, without modifications in the rest of the variables. In no obese individuals a bigger propensity to the cardiometabolic risk was observed. The index of greasy mass did not show significant correlation with the rest of anthropometric parameters. There is a narrow correlation among individuals with altered abdominal waist and the criteria established for the diagnosis of metabolic syndrome. Conclusions: the perimeter of waist constitutes a parameter of essential measure in the obese patient's evaluation, independently of the IMC, since it has been demonstrated a positive association between abdominal obesity and cardiometabolic risk.